Perilaku Bunuh Diri pada Remaja : Systematic Literature Review - Milladina Prabasanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Suicidal behavior is the fourth leading cause of death in the world for children and adolescents and is ranked 17th as the leading cause of death throughout life. This study aims to determine the factors associated with suicidal behavior in adolescents. Method: This study was conducted using a systematic literature review method by collecting data through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method for studies that study factors associated with suicidal behavior. The literature search strategy that will be used for the study was carried out by accessing the ScienceDirect, PubMed, Scopus database. Results: The results of the study showed that out of 9 research articles (2019-2024), shows that the correlation between depression, anxiety disorders, stress and bullying factors with suicidal behavior in adolescent each has a p-value (<0,001; <0,485; NA; <0,001). Conclusion: Based on the results of the meta-analysis conducted on 9 reseacrch artikels, it was concluded that there is a significant relationship between depression and bullying and suicidal behavior in adolescents. While the anxiety disorders and stress factors are considered not to have significant relationship with suicidal behavior.